Oceanity and continentality climate indices in Pakistan - Gadiwala, Muhammad Sohail; Burke, Farkhunda; Alam, Muhammad Touseef; ul-Huda, Syed Nawaz; Azam, Muhammad (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
Conceptually, the influence of oceans and continents plays key roles in the climate of any region. This study considers continentality and oceanity thermal climate index and focuses on the synoptic classification of Pakistan. The country has a diversified geographic relief which has profound influence on its climate from region to region. While its more than 990 km long coastal belt has wetter maritime condition, its interior belt is under the influence of arid and semi arid conditions and its higher altitude region has a hyper-arid climate. Marsz, also called Kerner Oceanity and Conrad Continentality Indices were calculated for Pakistan using the country’s temperature annual range data of the past fifty years (1961-2010) at 51 climate stations. When correlations between the two continental indices are compared, it indicates that a large area of Pakistan has continental climate. This comparison may be beneficial for Pakistan’s energy reforms and agricultural sectors.